2017
DOI: 10.5796/electrochemistry.85.13
|View full text |Cite
|
Sign up to set email alerts
|

Selective Determination of Nicotinamide Adenine Dinucleotide in the Presence of Ascorbic Acid and Uric Acid at a Long-Length Carbon Nanotube Electrode

Abstract: Selective electrochemical determination of nicotinamide adenine dinucleotide (NADH) in the presence of ascorbic acid (AA) and uric acid (UA) at a long-length multi-walled carbon nanotube (CNT) electrode is presented. We demonstrate the effectiveness of CNT length toward the electrochemical response due to oxidation of NADH. The long-length CNT is 200 µm (average), whereas normal-length CNT as a comparison is 1 µm (average). In differential pulse voltammetry, the current peaks due to NADH, AA, and UA at long-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The tested solutions were: 1 mM N , N , N ′, N ′-tetramethyl- p -phenylenediamine (TMPD) in 0.1 M KCl, 1 mM Ru(NH 3 ) 6 Cl 3 3+/2+ (RuHex) in 0.1 M KCl, 1 mM Dopamine in pH 7 phosphate buffer solution/0.1 M KCl (PBS), 1 mM β -Nicotinamide adenine dinucleotide (NADH) in pH 7 PBS/0.1 M KCl, 1 mM Capsaicin in 0.1 M HPO 4 , and 1 mM Ascorbic acid in pH 7 PBS/0.1 M KCl. The following diffusion coefficients were used in this work (cm 2 s −1 ): 6.74 × 10 −6 for dopamine [ 21 ], 7.40 × 10 −6 for NADH [ 22 ], 9.1 × 10 −6 for RuHex [ 23 ], 6.32 × 10 −6 for TMPD [ 24 ], 7.03 × 10 −6 for capsaicin, and 1.42 × 10 −6 for ascorbic acid [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The tested solutions were: 1 mM N , N , N ′, N ′-tetramethyl- p -phenylenediamine (TMPD) in 0.1 M KCl, 1 mM Ru(NH 3 ) 6 Cl 3 3+/2+ (RuHex) in 0.1 M KCl, 1 mM Dopamine in pH 7 phosphate buffer solution/0.1 M KCl (PBS), 1 mM β -Nicotinamide adenine dinucleotide (NADH) in pH 7 PBS/0.1 M KCl, 1 mM Capsaicin in 0.1 M HPO 4 , and 1 mM Ascorbic acid in pH 7 PBS/0.1 M KCl. The following diffusion coefficients were used in this work (cm 2 s −1 ): 6.74 × 10 −6 for dopamine [ 21 ], 7.40 × 10 −6 for NADH [ 22 ], 9.1 × 10 −6 for RuHex [ 23 ], 6.32 × 10 −6 for TMPD [ 24 ], 7.03 × 10 −6 for capsaicin, and 1.42 × 10 −6 for ascorbic acid [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…[2,3] In particular, NAD + determines the activity of enzymes, such as sirtuin enzymes, which are crucial to cellular metabolism, cell survival, and DNA repair. [2,3,6] This has become apparent as the decline of the cofactor has been attributed to various disease states, such as cardiovascular disease, diabetes, and kidney failure. [2,3,6] This has become apparent as the decline of the cofactor has been attributed to various disease states, such as cardiovascular disease, diabetes, and kidney failure.…”
Section: Introductionmentioning
confidence: 99%
“…[1] NAD + /NADH cofactor is critical for the success of the catalytic behavior of dehydrogenase enzymes, while also functioning as a biomarker within various systems and a regulatory agent for post-translational protein modifications. [2,3] In particular, NAD + determines the activity of enzymes, such as sirtuin enzymes, which are crucial to cellular metabolism, cell survival, and DNA repair. [4,5] The pyridine nucleotide is essential for the production and consumption of energy, and decreases in abundance as we age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27) Furthermore, we demonstrated that a long-length CNT electrode showed better electrochemical performance than its normal-length counterparts. [28][29][30] Therefore, we would like to extend the possibility of the CMC/long-length CNT electrode. We demonstrate the selective determination with a CNT electrode of rutin in the presence of ascorbic acid (AA), which now often coexists with rutin in soba tea in a PET bottled beverage.…”
mentioning
confidence: 99%